2011
DOI: 10.1007/s00122-011-1589-5
|View full text |Cite
|
Sign up to set email alerts
|

Rye-derived powdery mildew resistance gene Pm8 in wheat is suppressed by the Pm3 locus

Abstract: Genetic suppression of disease resistance is occasionally observed in hexaploid wheat or in its interspecific crosses. The phenotypic effects of genes moved to wheat from relatives with lower ploidy are often smaller than in the original sources, suggesting the presence of modifiers or partial inhibitors in wheat, especially dilution effects caused by possible variation at orthologous loci. However, there is little current understanding of the underlying genetics of suppression. The discovery of suppression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 17 publications
2
40
0
2
Order By: Relevance
“…This may be attributed to modulation of gene expression which sometimes occurs when resistance genes are introgressed from species of lower ploidy to higher ploidy. The possibilities of suppression of phenotypic effects in wide crosses of wheat at both interspecific and intergeneric categories have previously been reported [9], [39], [40], [41].…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to modulation of gene expression which sometimes occurs when resistance genes are introgressed from species of lower ploidy to higher ploidy. The possibilities of suppression of phenotypic effects in wide crosses of wheat at both interspecific and intergeneric categories have previously been reported [9], [39], [40], [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, the opposite was observed, with Pm8 providing additional resistance in the backgrounds of both Pm3 and the 1AS QTL from Naxos. As McIntosh et al (2011) suggested that translation of Pm3 is necessary for Pm8 suppression, we may conclude that the Pm3 allele of SHA3/CBRD is likely not functional. But this requires further investigations that are beyond the scope of this paper.…”
Section: Effect Of Race-specific Genesmentioning
confidence: 99%
“…At present, 60 resistance genes or alleles at 49 loci conferring resistance to PM ( Pm1 – Pm53 , Pm18  =  Pm1c , Pm22  =  Pm1e , Pm23  =  Pm4c , and Pm31  =  Pm21 ) have been identified from different wheat sources [2, 3]. Of these genes, 31 were derived from common wheat and the remainder were derived, or putatively derived, from wild relatives.…”
Section: Introductionmentioning
confidence: 99%